On the origin of dynamic Ron in commercial GaN-on-Si HEMTs. (February 2018) - Karboyan, Serge; Uren, Michael J.; Manikant; Pomeroy, James W.; Kuball, Martin
Abstract: There are huge differences in dynamic on-resistance Ron, also known as current-collapse, between current GaN power HEMT technologies. Here we illustrate this fact with dynamic Ron measurements on two commercially available devices from 2 different manufacturers, with one showing more than a factor of 2 increase in dynamic Ron after OFF-state drain bias (type 1) and the other one < 15% change. HTRB stress for 1000 h and 3000 h on type 1 and type 2 respectively was found to only make subtle changes to dynamic Ron, with type 1 still showing a much larger dynamic Ron than type 2. A model for dynamic Ron is presented based on a floating, highly resistive, epitaxial buffer whose potential is determined by parasitic leakage paths. The difficulty in controlling local leakage paths can explain the problems that manufacturers are still finding in suppressing dynamic Ron . Highlights: Comparison of dynamic Ron in two commercially available devices from 2 different manufacturers. Factor of 2 increase in dynamic Ron after OFF-state bias for type 1 devices and less than 15% increase for type 2 devices. HTRB stress for 1000 h and 3000 h on type 1 and type 2 respectively was found to only make subtle changes to dynamic Ron . A model based on a floating epitaxial buffer is presented where the potential is determined by parasitic leakage paths. The difficulty in controlling leakage paths explains the problems that manufacturers are still finding in suppressing dyn-Ron .